FORMATION AND DEVELOPMENT TRENDS OF MARKETING IN UKRAINE: A MODERN VIEW OF THE THEORY AND PRACTICE OF MARKETING - KOVALCHUK, Svitlana; ZABURMEKHA, Yevgeniya; SHEMCHUK, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of writing the article is to determine the evolutionary and innovative trends in the formation and formation of the theory and practice of Ukrainian marketingMarketing is considered as a strategic function that determines the policy, style and nature of enterprise management. The implementation of the marketing concept in the practical activities of enterprises and organizations enables the processes of forming rational strategic programs, creates prerequisites for adaptive and proactive response to changes in the market situation, quick orientation in difficult conditions of market competition. A comparative characterization of various scientific schools of marketing and their influence on the formation of the Ukrainian school, taking into account its peculiarities, was carried out. Stages of development of Ukrainian marketing are presented. Formulated problems related to the organization of marketing activities by Ukrainian enterprises.The Ukrainian marketing school has a well-formed fundamental approach to theoretical issues. The study of theoretical achievements in the field of marketing and the practice of Ukrainian marketing activity, the elimination of problems that slow down its development and taking into account modern trends in the development of marketing strategies under the influence of turbulent changes in the market environment will allow creating a powerful practical basis for the development and implementation of innovative methods, as well as ensuring the proactive development of Ukrainian school of marketing and implementation of its achievements in the international scientific society.
Keywords: marketing; marketing school; phasing; problems of organizing marketing activities